Secondary Rhinoplasty On Cleft Lip Nose - Sudjatmiko, Gentur; Kreshanti, Prasetyanugraheni (Jurnal Plastik Rekonstruksi, 2012)
By definition a secondary rhinoplasty is a procedure to correct the nasal shape deformity in cleft lip patients, which is performed not in conjunction with the labioplasty procedure. Several important factors to be considered in doing rhinoplasty procedures in cleft lip patients are: (1) Open rhinoplasty is more beneficial in assessing the whole nasal deformity, especially the nasal cartilage in cleft lip patients, (2) Releasing the latero-superior cartilage attached to the nasal bone and skin, which caused webbing inside the nostrils, (3) Addition of strut in columella as a pillar to adjust the dropping nose to the upright position, (4) Addition of cartilage plate whenever needed in the cleft side, (5) The nostril narrowing on the cleft side could be reduced by enlarging the nostril diameter, (6) The new nostril shape is maintained using a device (nasal retainer) for several weeks until the healing process is achieved, (7) The suture removal in nose is not as easy as of those in lip. The suture removal could be performed under mild sedation especially in uncooperative patients.